Pengaruh Customer Relationship Management (CRM), Kualitas Pelayanan Dan Nilai Pelanggan Terhadap Loyalitas Pelanggan HOTEL KERINCI DI KOTA SUNGAI PENUH - ENNY SESTRIYENTI (JURNAL ILMU PENGETAHUAN & SISTEM INFORMASI (JIPSI), 2018)
Issues raised in this study are variables that affect the Kerinci Hotel Customer Loyalty In Sungai Penuh, variable research is Customer Relationship Management (CRM), Quality of Service and Customer Value. This study aims to reveal the effect of Customer Relationship Management (CRM), Quality of Service and Customer Value on Customer Loyalty simultaneously Hotel Kerinci In River City Full, Effect of Customer Relationship Management (CRM), Quality of Service and Customer Value partially on Customer Loyalty Hotel Kerinci in Sungai Penuh. The study population was all Customer Hotel Kerinci In Sungai Penuh samples in this study were taken bersadarkan accidental sampling method. Sampling Accidental sampling is based on chance and set as many as 100 customers . Data were collected using the Likert Scale questionnaire models. Then the data were analyzed using correlation techniques and multiple linear regression with the help of the computer program SPSS for Windows version 20 o'clock. The results of the analysis indicate that there is the contribution of Customer Relationship Management (CRM), Quality of Service and Customer Value on Customer Loyalty simultaneously Hotel Kerinci In Sungai Penuh by 52%%. When viewed its influence on the regression equation Y = X1 + 7.832 + 0.194 + 0.278 0 298X2 X3 Based on these results, the researchers concluded that there is significant influence Customer Relationship Management (CRM), Quality of Service and Customer Value either simultaneously or partially on Customer Loyalty Hotel Kerinci In Sungai Penuh. The authors suggest to the parties concerned to improve Customer Relationship Management (CRM), Quality of Service and Customer Value, Customer Loyalty hotel so Kerinci In Sungai Penuh is increased significantly. This does not mean that other factors not examined ignored. Keywords: Customer Relationship Management (CRM), Service Quality, Customer Value danloyalitas customers